Increased incidence of injury among runners with COVID-19 - Toresdahl, B. G.; Robinson, J. N.; Kliethermes, S. A.; Metzl, J. D.; Dixit, S.; Quijano, B.; Fontana, M. A. (Sports Health: A Multidisciplinary Approach, 2021)
Background: Coronavirus disease 2019 (COVID-19) affects multiple organ systems. Whether and how COVID-19 affects the musculoskeletal system remains unknown. We aim to assess the association between COVID-19 and risk of injury. Hypothesis: Runners who report having COVID-19 also report a higher incidence of injury. Study Design: Cross-sectional study. Level of Evidence: Level 4. Methods: An electronic survey was distributed from July through September 2020, by New York Road Runners, ASICS North America, race medical directors, and through social media. Inclusion criteria were runners 18 years or older who had participated in =1 race (running or triathlon) in 2019. Results: A total of 1947 runners participated and met inclusion criteria. Average age was 45.0 (SD, 12.2) years and 56.5% were women. A total of 123 (6.3%) runners self-reported having COVID-19; 100 (81%) reported their diagnosis was from a laboratory test (polymerase chain reaction or antibody) and 23 reported being diagnosed by a medical professional without confirmatory laboratory testing. Since March 2020, 427 (21.9%) reported an injury that prevented running for at least 1 week, including 38 of 123 (30.9%) who self-reported having COVID-19 and 389 of 1435 (21.3%) who did not report having COVID-19 (P = 0.01). After adjusting for age, sex, the number of races in 2019, and running patterns before March 2020, runners who self-reported a diagnosis of COVID-19 had a higher incidence of injury compared with those who did not (odds ratio, 1.66; 95% CI, 1.11-2.48; P = 0.01). Conclusion: Injuries were more often self-reported by runners with laboratory-confirmed or clinically diagnosed COVID-19 compared with those who did not report COVID-19. Given the limitations of the study, any direct role of COVID-19 in the pathophysiology of injuries among runners remains unclear. Clinical Relevance: Direct and indirect musculoskeletal sequelae of COVID-19 should be further investigated, including the risk of exercise- and sports-related injury after COVID-19.